Perceived Stress Levels in Adult Patients With Uveitis - Grajewski, Rafael S.; Boelke, Anna C.; Adler, Werner; Pape, Arina; Schroedl, Falk; Hueber, Arno; Albus, Christian; Vitinius, Frank; Heindl, Ludwig M. (Frontiers in Psychiatry, 2020)
Abstract: Background: The aim of this study was to examine perceived stress levels in adult patients with uveitis. Patients and Methods: 173 adult consecutive uveitis patients (age range 18 to 85 years) were analyzed in a cross-sectional design for their perceived stress, according to the perceived stress questionnaire (PSQ). Stress levels were classified into normal stress, moderate stress, and high stress. Results: In the majority of uveitis patients a normal stress level (82%) within the last 2 years was detected. In a subgroup analysis, perceived stress of the patients with active uveitis compared with patients with non-active uveitis was significantly higher within the last 2 years (n=80 active/n=45 non-active; p=0.005). Conclusions: Overall 18% of the uveitis patient had raised perceived stress, similar to the general population but patients with active uveitis were significantly more stressed. Therefore, consideration of stress levels may be important in the therapy of uveitis patients. Keywords: Uveitis – Stress – Perceived Stress Questionnaire (PSQ) – Inflammatory Disease-Disease Activity Running head: Perceived stress in uveitis patients